Literatur Review: EFEKTIVITAS ANTIBAKTERIAL DAUN JAMBU BIJI (Psidi guajava L.) TERHADAP Streptococus mutans PENYEBAB KARIES GIGI - I Gede Bayu Surya Ekayana (Departement of Pharmacy, Faculty of Mathematics and Natural Science, Udayana University, 2025)
Oral health is an essential component of overall health and significantly affects quality of life. One of the most common oral health problems is dental caries, which is the destruction of tooth tissue caused by enamel demineralization triggered by acid produced from carbohydrate metabolism by plaque bacteria, particularly Streptococcus mutans. Guava leaves (Psidium guajava L.) are known to contain active compounds with antibacterial properties. Research has shown that these active compounds can inhibit the growth of Streptococcus mutans and disrupt dental biofilm formation, making them a potential preventive agent against caries. Articles were collected from PubMed, Google Scholar, and ScienceDirect using Boolean search techniques. Of the 538 articles identified, 10 were selected based on inclusion criteria and topic relevance. The review results show that guava leaf extract can reduce Streptococcus mutans colony counts both in vitro and in vivo, demonstrating effectiveness comparable to 0.2% chlorhexidine without adverse side effects. Furthermore, combining guava leaf extract with other agents, such as nanosilver and guava bark extract, has been shown to enhance antibacterial activity through synergistic mechanisms. Therefore, it can be concluded that guava leaves have strong potential as a natural, effective, and safe alternative for the prevention of dental caries.